Guiding lead optimization with GPCR structure modeling and molecular dynamics. (October 2016) - Heifetz, Alexander; James, Tim; Morao, Inaki; Bodkin, Michael J; Biggin, Philip C.
Graphical abstract: Highlights: Why GPCR modeling approaches are used in the lead optimization stage of drug discovery? What can we learn from molecular dynamics simulations? Hierarchical GPCR modeling protocol (HGMP). Examplification of the HGMP application in three drug discovery projects. Abstract : G-protein coupled receptor (GPCR) modeling approaches are widely used in the hit-to-lead and lead optimization stages of drug discovery. Modern protocols that involve molecular dynamics simulation can address key issues such as the free energy of binding (affinity), ligand-induced GPCR flexibility, ligand binding kinetics, conserved water positions and their role in ligand binding and the effects of mutations. The goals of these calculations are to predict the structures of the complexes between existing ligands and their receptors, to understand the key interactions and to utilize these insights in the design of new molecules with improved binding, selectivity or other pharmacological properties. In this review we present a brief survey of various computational approaches illustrated through a hierarchical GPCR modeling protocol and its prospective application in three industrial drug discovery projects.